2021
DOI: 10.2991/assehr.k.211021.013
|View full text |Cite
|
Sign up to set email alerts
|

Argumentation Skills: An Analysis on EFL Students’ Essays Based on Toulmin’s Model of Argument

Abstract: Writing argumentative essays is not only challenging because the writers must have adequate knowledge on the topic but also, they must provide strong arguments to convince the readers. This study analyzes the argumentation skills of advanced level students in writing the content of an argumentative essay. The design of the research was descriptive quantitative involving 60 argumentative essays written by 30 students of the Academic Writing course. The data were analyzed by using a scoring guide referring to To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…As Jumariati, Febriyanti, and Rizki (2021) noted, for an argument to convince, it must be bolstered by strong supporting data. Moreover, they also contended that a good and successful argument needs to include a rebuttal because possible objections are anticipated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Jumariati, Febriyanti, and Rizki (2021) noted, for an argument to convince, it must be bolstered by strong supporting data. Moreover, they also contended that a good and successful argument needs to include a rebuttal because possible objections are anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, Gunderman and Chou admit that while merely studying the elements of argumentation may be enough to think and reason well, it certainly helps. Jumariati, Febriyanti, and Rizki (2021) measured the argumentative skills of students of an academic writing course at a university in Indonesia using their argumentative essays and a scoring rubric, which rubric was based on Toulmin's elements of argumentation. Jumariati, Febriyanti, and Rizki found that most of the students gave complete and precise claims and data.…”
Section: Frameworkmentioning
confidence: 99%
“…It indicates that the participants might doubt that they cannot achieve the peak of CCL performance. It can be understood that the argumentative genre is one of the most difficult writings (Ferretti et al, 2007;Jumariati et al, 2021). However, the average gap between the current and desired conditions of each indicator across the seven domains revealed that CCL skills are highly necessary in the EFL classes, in this case, in the teaching of one or two-sided argumentative writing.…”
Section: The Needs Of Critical and Creative Literacy In The Argumenta...mentioning
confidence: 99%
“…Toulmin's Model of Logic-Based Argumentation sheds light on the impact of cultural and educational backgrounds on an individual's preferred persuasion techniques, reasoning patterns, and argumentation styles. This underscores the significant influence of cultural context on these aspects of argumentation (Jumariati et al, 2021). The acquisition of this knowledge holds significant value for educators and curriculum designers, as it empowers them to tailor their teaching methodologies to effectively address the distinctive requirements of the learners.…”
Section: Introductionmentioning
confidence: 95%